Sustainable luxury purchase behavior in the Post-Pandemic Era: a grounded theory study in China - Yang, Huaxia; Su, Xiaoyan; Shion, Kojo (Frontiers in Psychology, 2023)
Despite the increasing sustainable practices from the luxury industry, research show little evidence on consumers’ reactions toward sustainable luxury. This paper aims at understanding changes in consumers’ consumption behavior toward sustainable luxury fashion products in the Post-Pandemic Era. We use exploratory qualitative research conducted by semi-structured in-depth interviews involving luxury consumers in China based on grounded theory. With the help of Nvivo12, the interview data is coded and analyzed to identify the influencing attitude and intention of sustainable luxury fashion in China in the Post-Pandemic Era. The findings show that hedonic value, uniqueness value, social value, functional value (practicality, quality, and value for money), health value and sustainable value affect purchase intention toward sustainable luxury in the Post-Pandemic Era. A theoretical model is built to systematically analyze the determinants of purchase behavior. This study will contribute to the literature on sustainable luxury fashion behaviors by performing in-depth interviews in the Post-Pandemic Era. Besides, the findings provide guidance for industries to make customer-based sustainable strategies when practicing sustainable development in luxury fashion in China.